Phosphorylation of MAD2 at Ser195 Promotes Spindle Checkpoint Defects and Sensitizes Cancer Cells to Radiotherapy in ATM Deficient Cells - Wang, Yang; Yu, Tianyu; Han, Yi; He, Yazhi; Song, Yiran; Guo, Leiming; An, Liwei; Yang, Chunying; Wang, Feng (Frontiers in Cell and Developmental Biology, 2022)
The spindle assembly checkpoint (SAC) is a critical monitoring device in mitosis for maintenance of genomic stability. Specifically, SAC complex is composed of by several factors including Mad1, Mad2 and Bub1. Ataxia-Telangiectasia Mutated (ATM) kinase plays crucial roles in initiating DNA damage responses. Despite the regulatory roles of ATM for Mad1 has been elucidated, its effect on Mad2-dependent functions remain elusive. Here, we showed that ATM deficiency can result in severe checkpoint defects. Mechanistically, we found that phosphorylation of Mad2 is aberrantly increased in ATM-loss cells. Point-mutation analysis further revealed that Serine 195 was mainly mediated Mad2 phosphorylation upon ATM ablation. Functionally, the phosphorylation of Mad2 causes accelerated DNA damage repair capacity and is related to the resistance to cancer cell radiotherapy. Altogether, this study unveils the key regulatory role of Mad2 phosphorylation in checkpoint defects and DNA damage repair in ATM-loss cells.